Ефективність використання соціальної та екологічної відповідальності в управлінні агропідприємством - Хаянок, Т. М.; Hayanok, T. (Дніпровський державний аграрно-економічний університет, 2015)
Досліджено науково-теоретичні засади ефективності використання соціальної та екологічної відповідальності в управлінні, що передбачають упровадження концепції сталого розвитку в діяльність аграрних підприємств. Узагальнюючи характер становлення концепції сталого рівня у світі та в Україні, автор систематизував історичні етапи розвитку соціальної та екологічної відповідальності в управлінні підприємствами. Визначено можливості отримання та підвищення ефективності діяльності агропідприємств від впровадження в управління соціальної та екологічної відповідальності. Scientific and theoretical principles of effective use of social and environmental responsibility in management, involving the implementation of sustainable development activities in agricultural enterprises. Summarizing the character formation of the concept of sustainable development in the world and inUkraine, the author systematized historical stages of social and environmental responsibility in the management of enterprises. Defined and increasing opportunities for economic, social and environmental efficiency of agro from the introduction and use in the management of sustainable (sustainable) development. The factors which necessitated the introduction of policies of social and environmental responsibility in the activities of Ukrainian agricultural enterprises that need improving institutional and organizational foundations of business and regulation mechanisms for the implementation of sustainable development. Author substantiated efficiency of social and environmental responsibility in the management of agricultural enterprise that provides the experience and practice of socially-oriented foreign and domestic companies, as well as the characteristics and importance of management on the basis of sustainable development for economic benefits, the formation of public awareness and the conservation and restoration of ecosystems the planet.
Efficiency of social and environmental responsibility in management agribusiness
Keywords: соціальна відповідальність; social responsibility; екологія; ecology; ефективність; efficiency; концепція стійкого розвитку; concept of sustainable development; управління аграрним підприємством; management of agricultural enterprise